Bi-isotype immunoglobulins enhance antibody-mediated neutrophil activity against Plasmodium falciparum parasites - Ogwang, Rodney; Murugu, Lewis; Nkumama, Irene N.; Nyamako, Lydia; Kai, Oscar; Mwai, Kennedy; Murungi, Linda; Idro, Richard; Bejon, Philip; Tuju, James; Kinyanjui, Sam Muchina; Osier, Faith H. A. (Frontiers in Immunology, 2024)
Background: Malaria remains a major global health priority and monoclonal antibodies (mAbs) are emerging as potential new tools to support efforts to control the disease. Recent data suggest that Fcdependent mechanisms of immunity are important mediators of protection against the blood stages of the infection, but few studies have investigated this in the context of mAbs. We aimed to isolate mAbs agnostic to cognate antigen that targeted whole merozoites and simultaneously induced potent neutrophil activity measured by the level of ROS production within the antibody-dependent respiratory burst assay (ADRB). Methods: We used samples from semi-immune adults living in coastal Kenya to isolate mAbs that induce merozoite specific ADRB activity. We then tested whether modifying the expressed IgG1isotype to an IgG-IgA Fc-region chimera would enhance the level of ADRB activity.We isolated a panel of nine mAbs with specificity to whole merozoites. Mab J31 induced ADRB activity in a dose dependent fashion. Compared to IgG1, our modified antibody IgG-IgA biisotype induced higher ADRB activity across all concentrations tested. Further, a negative hook effect was observed at high IgG1mAb concentrations (i.e. >200 µg/ml), but this was reversed by Fc modification. We identified MSP3.5 as the potential cognate target of mAb J31. Conclusion: We demonstrate an approach to engineering of mAbs with enhanced ADRB potency against blood stage parasites.